2022
DOI: 10.1039/d2sc01398c
|View full text |Cite
|
Sign up to set email alerts
|

Atomic and structural modifications of two-dimensional transition metal dichalcogenides for various advanced applications

Abstract: Two-dimensional (2D) transition metal dichalcogenides (TMDs) and their heterostructures have attracted significant interest in both academia and industry because of their unusual physical and chemical properties. They offer numerous applications,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 291 publications
(421 reference statements)
0
31
0
Order By: Relevance
“…Research on 2D transition metal dichalcogenides (TMDs) has been dramatically increased during the last decade and, in that time, many research groups have demonstrated working transistors with these films [ 136 , 258 , 259 , 260 , 261 , 262 , 263 ]. Among TMDs, molybdenum disulfide (MoS 2 ) [ 22 , 259 , 263 ] and tungsten sulfide (WS 2 ) [ 264 ] are of particular interest for transistors, since they are naturally occurring layered crystals, are robust and relatively abundant, and present a wide band gap; nevertheless, many other TMDs are also readily being investigated [ 132 , 260 , 265 ]. One of the main issues with 2D TMD semiconductor FETs is finding a fitting insulator, whether in the top-gated or back-gated configuration, where the interface defect concentration is minimal and does not negatively impact transistor operation or its long-term reliability [ 21 , 266 , 267 ].…”
Section: Two-dimensional-material-based Gas Sensing Filmsmentioning
confidence: 99%
“…Research on 2D transition metal dichalcogenides (TMDs) has been dramatically increased during the last decade and, in that time, many research groups have demonstrated working transistors with these films [ 136 , 258 , 259 , 260 , 261 , 262 , 263 ]. Among TMDs, molybdenum disulfide (MoS 2 ) [ 22 , 259 , 263 ] and tungsten sulfide (WS 2 ) [ 264 ] are of particular interest for transistors, since they are naturally occurring layered crystals, are robust and relatively abundant, and present a wide band gap; nevertheless, many other TMDs are also readily being investigated [ 132 , 260 , 265 ]. One of the main issues with 2D TMD semiconductor FETs is finding a fitting insulator, whether in the top-gated or back-gated configuration, where the interface defect concentration is minimal and does not negatively impact transistor operation or its long-term reliability [ 21 , 266 , 267 ].…”
Section: Two-dimensional-material-based Gas Sensing Filmsmentioning
confidence: 99%
“…Two-dimensional (2D) layered transition metal dichalcogenides, MX 2 (M = Mo and W; X = S and Se), have emerged as promising materials for diverse applications owing to their rich surface chemistry, the presence of surface defects, and active edges. These materials possess many interesting properties, viz., thickness-dependent band transitions, high charge carrier mobility with a direct band gap, strongly bound excitons, ambipolar characteristics, and enhanced spin–orbit coupling. In contrast to their other 2D analogues, TMDs are chemically more versatile and active toward chemical modification. In TMDs, the intralayer M–X bonds are covalent in nature, whereas the layers are sandwiched and stacked together by weak van der Waals interactions. , The edge sites of TMDs possess high surface energy, which makes edges more active sites for chemical transformation . Furthermore, these TMDs are known to have a large number of chalcogenide vacancies considered as defect sites. , The properties of these TMDs are greatly dependent upon the nature of the surface and the presence of defect sites.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] Considerable efforts based on compositional or structural modi cation of MoS 2 have been devoted to boosting the electron/ion migration kinetics to achieve favorable sodium storage performance. 21 Conductive substrates (e.g., graphene, MXene, etc.) have been commonly incorporated to improve charge transfer and alleviate volume expansion, [22][23][24][25][26][27] which has been proven to make sense for enhancing rate capability and cycling lifespan.…”
Section: Introductionmentioning
confidence: 99%